Penerapan Gudang Pendingin Bawang Merah (Allium ascalonicum L.) untuk Pengendalian Pasokan (Studi Kasus: Kabupaten Bantul dan Kabupaten Cirebon) - Shalihy, Wildan (Perum BULOG, 2016)
Indonesia experiencing production surplus of onions, meanwhile the market price still fluctuating. There is an indication that the onion’s supply chain/distribution has not run well. Therefore, supply chain analysis is needed to determine the distribution of onions. Cold storage is the best storage technology to maintain onion`s quality and increasing the value added. The purpose of this research is to map the supply chain of onion in Bantul and determine the economic feasibility of onion’s cold storage in Cirebon so that the results of this research can be used as a reference for the development of cold storage facility in Bantul. This research uses supply chain performance analysis method, marketing efficiency, Hayami value added method and basic cost analysis. The analysis shows that there are four patterns of marketing channels in Bantul, the highest marketing margin held by retailers by Rp 4.500,00 and farmer’s share is highest in grade A as big as 66,67 percent, π/c value was centrally in distribution access no 4 by 13,90. The operational cost of cold storage is Rp 769,00/month/kg. The additional cost of cold storage is Rp 9.993,00/kg and traditional storage is Rp 6.900,00/kg with initial cost of Rp 35.000,00